2015
DOI: 10.1007/s00467-015-3232-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary fibrogenic cytokines ET-1 and TGF-β1 are associated with urinary angiotensinogen levels in obese children

Abstract: Whereas the initial hypothesis of higher levels of urinary fibrogenic cytokines in obese children was not confirmed in our study, both TGF-β1 and U-ET-1 levels were associated with U-AGT level, which likely reflects an early interplay between tissue remodeling and RAAS in obesity-related kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Based on these published data and on the negative impact that obesity has on the kidney [2], we would expect that overweight/obese children had higher U-AGT than age-matched controls of normal weight. However, as recently reported by our group [36], we observed no significant differences in U-AGT between normal and overweight/obese children. In this study, we further extended this result and clarified that it is observed regardless of the obesity index considered: classes of BMI or tertiles of WHtR or percent body fat mass.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Based on these published data and on the negative impact that obesity has on the kidney [2], we would expect that overweight/obese children had higher U-AGT than age-matched controls of normal weight. However, as recently reported by our group [36], we observed no significant differences in U-AGT between normal and overweight/obese children. In this study, we further extended this result and clarified that it is observed regardless of the obesity index considered: classes of BMI or tertiles of WHtR or percent body fat mass.…”
Section: Discussionsupporting
confidence: 81%
“…Also, we Mean ± standard deviation or n (%). BMI z-score classification is according to WHO criteria (normal weight, overweight, and obesity) [32] BMI body mass index, WHtR waist-to-height ratio, MAP mean arterial pressure a According to the population-based Canadian reference curves [30] recently reported [36] that urinary excretion of the fibrogenic cytokines endothelin-1 (ET-1) and transforming growth factor-β1 (TGF-β1) was not increased in obese children in our cohort; indeed, they showed lower levels of urinary ET-1 and TGF-β1 than those of normal weight. Furthermore, U-AGT was associated with urinary excretion of ET-1 and TGF-β1 [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PDGF, TNF-α, interleukin (IL)-6, IL-1β, and IL-13 are also key pro-fibrotic mediators, pharmacological inhibition, and/or gene deletion of these cytokines prevented the progression of hepatic fibrosis (Schwabe et al 2003;Kaviratne et al 2004;Sudo et al 2005). Furthermore, vasoconstrictors (e.g., norepinephrine, angiotensin II (Ang-II)) (Oben and Diehl 2004;Han et al 2017), and endothelin (ET)-1 (Cho et al 2000;Correia-Costa et al 2016) exert potent fibrogenic activities, while vasodilators (e.g., nitric oxide (NO), relaxin) have opposite actions (Iwakiri 2015).…”
Section: Hepatic Fibrosismentioning
confidence: 99%